Makna Komitmen dalam Lirik Lagu “Promise” Karya EXO: (Analisis Semiotika Charles Sanders Peirce) - I Wayan Suartawan; Melina Sefani; Astuti Wijayanti (Lembaga Pengembangan Kinerja Dosen, 2026)
Songs as a form of artistic expression have the power to convey deep emotional messages. One of the works that is full of meaning is